Commodities for the Long Run. Issue 2 (1st April 2018) - Levine, Ari; Ooi, Yao Hua; Richardson, Matthew; Sasseville, Caroline
Abstract : Using a novel dataset consisting of daily futures prices going back to 1877, we find that returns of commodity futures indices have, on average, been positive over the long run. Although return premiums are associated with both carry and spot returns, commodity returns in different economic states (inflation up/down, expansion/recession) vary mostly as a result of moves in the underlying spot price. These economic states are important drivers of commodity returns, even after conditioning on whether commodity markets are in backwardation or contango. The evidence supports commodities as a potentially attractive asset class in portfolios of stocks and bonds. Abstract : Disclosure: Three of the authors are employed at AQR Capital Management, a global investment management firm, which may or may not apply similar investment techniques or methods of analysis as described herein. The views expressed here are those of the authors and not necessarily those of AQR. Editor's Note This article was externally reviewed using our double-blind peer-review process. When the article was accepted for publication, the authors thanked the reviewers in their acknowledgments. William Fung was one of the reviewers for this article. Submitted 27 October 2016 Accepted 20 December 2017 by Stephen J. Brown